Impact of corticosteroid therapy on the outcomes of hepatocellular carcinoma treated with immune checkpoint inhibitor therapy. Issue 2 (7th October 2020) - Pinato, David J; Kaseb, Ahmed; Wang, Yinghong; Saeed, Anwaar; Szafron, David; Jun, Tomi; Dharmapuri, Sirish; Naqash, Abdul Rafeh; Muzaffar, Mahvish; Navaid, Musharraf; Khan, Uqba; Lee, ChiehJu; et al.
Abstract : The impact of corticosteroid therapy (CT) on efficacy of immune checkpoint inhibitors (ICI) is undefined in hepatocellular carcinoma (HCC). We evaluated whether CT administered at baseline (bCT) or concurrently with ICI (cCT) influences overall (OS), progression-free survival (PFS) and overall response rates (ORR) in 341 patients collected across 3 continents. Of 304 eligible patients, 78 (26%) received > 10 mg prednisone equivalent daily either as bCT (n=14, 5%) or cCT (n=64, 21%). Indications for CT included procedure/prophylaxis (n=37, 47%), management of immune-related adverse event (n=27, 35%), cancer-related symptoms (n=8, 10%) or comorbidities (n=6, 8%). Neither overall CT, bCT nor cCT predicted for worse OS, PFS nor ORR in univariable and multivariable analyses (p>0.05). CT for cancer-related indications predicted for shorter PFS (p<0.001) and was associated with refractoriness to ICI (75% vs 33%, p=0.05) compared with cancer-unrelated indications. This is the first study to demonstrate that neither bCT nor cCT influence response and OS following ICI in HCC. Worse outcomes in CT recipients for cancer-related indications appear driven by the poor prognosis associated with symptomatic HCC.